Hyperinvasiveness of Listeria monocytogenes sequence type 1 is independent of lineage I‐specific genes encoding internalin‐like proteins. Issue 7 (17th January 2019) - Gözel, Bulent; Monney, Camille; Aguilar‐Bultet, Lisandra; Rupp, Sebastian; Frey, Joachim; Oevermann, Anna
Abstract: Listeriosis is a severe disease caused by the opportunistic bacterial pathogen Listeria monocytogenes ( L. monocytogenes ). Previous studies indicate that of the four phylogenetical lineages known, lineage I strains are significantly more prevalent in clinical infections than in the environment. Among lineage 1, sequence type (ST1) belongs to the most frequent genotypes in clinical infections and behaves hyperinvasive in experimental in vitro infections compared to lineage II strains suggesting that yet uncharacterized virulence genes contribute to high virulence of certain lineage I strains. This study investigated the effect of four specific lineage I genes encoding surface proteins with internalin‐like structures on cellular infection. CNS derived cell lines (fetal bovine brain cells, human microglia cells) and non‐CNS derived cell lines (bovine macrophage cells, human adenocarcinoma cells) that represent the various target cells of L. monocytogenes were infected with the parental ST1 strain and deletion mutants of the four genes. Despite their association with lineage I, deletion of the four genes investigated did not dampen the hyperinvasiveness of the ST1 strain. Similarly, these genes did not contribute to the intracellular survival and intercellular spread of L. monocytogenes ST1, indicating that these genes may have other functions, either during the infection process or outside the host. Abstract : Sequence type (ST1) of Listeria monocytogenes lineage I belongs to the most frequent genotypes in clinical infections and behaves hyperinvasive in experimental in vitro infections compared to lineage II strains suggesting that yet uncharacterized virulence genes contribute to high virulence of certain lineage I strains. This study investigated the effect of four specific lineage I genes encoding surface proteins with internalin‐like structures on cellular infection. Despite their association with lineage I, deletion of the four genes did not affect the cellular infection of L. monocytogenes ST1, indicating that these genes may have other functions, either during the infection process or outside the host.